APPLE VARIETAL POOL AND BREEDING FOR THE BIOCHEMICAL COMPOSITION OF FRUIT - E. N. Sedov; M. A. Makarkina; Z. M. Serova (Вавиловский журнал генетики и селекции)
Fruit biochemical composition of the apple varietal pool was being studied for 58 years in the oldest pomological institution All Russia Research Institute for Fruit Crop Breeding. Contents of soluble dry matter, total sugar, titratable acids, pectin, ascorbic acid, and P-active substances have been studied. Directed apple breeding for higher content of ascorbic acid in fruit has been carried out since 1970. Biochemical compositions have been studied in 265 apple varieties from the Institute collection, 52 varieties raised at the Institute, and 1400 hybrid seedlings, including 373 selected elite ones. Sources of high contents of biochemically valuable substances and features of their inheritance have been determined amongst the apple varieties and hybrid seedlings. Varieties with high contents of sugars, ascorbic acid, and P-active substances in fruit, as well as with best sugar and acid proportions have been developed and included in the State Register of Breeding Achievements Recommended for Use. It is shown that apple breeding for fruit biochemical composition improvement has great prospects, since the introduction of such varieties would allow increasing the nourishing and preventive value of fruit without additional consumption of nonrenewable energy sources.